provide a method to reduce energy consumption in wireless sensor networks using DBSCAN clustering algorithm - Reza Molaee Fard (مدیریت مهندسی و رایانش نرم)
In this research, we evaluate energy efficient clustering methods in wireless sensor networks. The results of this study indicate that clustering by DBSCAN has a higher efficiency score than other clustering methods. The DBSCAN scored 99%, but the K-Means algorithm scored 76%. Also, the energy remaining in the network after the simulation is completed in routing with the new protocol is about 11% more than routing with EEHC and about 9% more than routing with LCA protocol. If we consider the lifespan of the network when the first node in the network is turned off, in the new protocol, the first node shuts down 6 seconds later than the EEHC protocol and 12 seconds later than the LCA‌ protocol. This means that on average, about 10% of network life has been increased with the new protocol. The I-LEACH protocol improves energy efficiency and longevity by working more in the same structures than the conventional LEACH protocol.